The impact of nutrition on quality of life of patients with hepatitis C. Issue 5 (September 2017) - Silva, Luciana D.; Bering, Tatiana; Rocha, Gifone A.
Abstract : Purpose of review: The aim of this study was to review the most recent aspects of nutrition and its impact on health-related quality of life (HRQOL) in patients with chronic hepatitis C (CHC). Recent findings: Low HRQOL scores have been found in all stages of hepatitis C virus (HCV) infection. Of the factors linked to HRQOL, three aspects should be emphasized, nutritional status, physical activity and mental health status. Regarding the nutrition and metabolic conditions, a broad spectrum of nutritional disorders may impact on HRQOL of patients with CHC. Summary: Malnutrition, which is a significant comorbidity in end-stage of all chronic liver diseases, has been recognized as a significant factor related to poor HRQOL. Of note, in individuals chronically infected with HCV, low muscle skeletal mass, an early indicator of undernourishment, precedes the development of cirrhosis. Because of the strict linkage between HRQOL, nutrition and physical activity, the assessment of the musculoskeletal system abnormalities in every patient with CHC, independently of the stage of the liver disease, is of utmost relevance. Maintenance of healthy skeletal muscle is essential to reduce the negative effects of sarcopenia on HRQOL. Otherwise, overweight/obesity and chronic HCV infection can cause insulin resistance, which has been associated with HRQOL impairment.